Phase transformations and microstructure evolutions during depressurization of hydrogenated Fe–Mn–Si–Cr alloy. (29th March 2023) - Varanasi, Rama Srinivas; Koyama, Motomichi; Saitoh, Hiroyuki; Utsumi, Reina; Sato, Toyoto; Orimo, Shin-ichi; Akiyama, Eiji
Abstract: Hydride formation and associated phase transformations have been extensively studied in pure Fe. However, the understanding of hydrogenation in Fe-based alloy systems is still lacking. Such an investigation is particularly important in the case of austenitic (face-centered cubic) steels given that hydrogen has been reported to alter the austenite phase stability. In the current work, we investigate the phase transformations associated with depressurization of non-hydrogenated and hydrogenated Fe–Mn–Si–Cr alloy (FMS) (Fe-28.84Mn-7.04Cr-6.14Si, in mass %) using in-situ x-ray diffraction technique. Additionally, we study the change in microstructure using electron backscatter diffraction (EBSD) and electron channeling contrast imagining (ECCI). Highlights: We report phase transformations during depressurization of non-hydrogenated (FMS) and hydrogenated (FMS H ) Fe–Mn–Si–Cr alloy. Constituent phase of FMS at 9 GPa, 973 K is HCP. Cooling and depressurization resulted in the formation of FCC + HCP phases. Cooling and depressurization of FMS H (from 9 GPa, 973 K) caused the transformation from DHCP + HCP → DCHP + HCP + FCC. Extensive microscopic and nanoscopic cracking have been observed in the depressurized FMS H . 3 microstructural morphologies in the depressurized FMS H : (1) Ultra-fine globular (2) Coarse lamellar (3) 'Fingerprint' like.